Leveraging Automation toward Development of a High-Throughput Gene Expression Profiling Platform. (March 2021) - Chen, Jing; Futran, Alan; Crithary, Austin; Li, Sha; Wolicki, Alex; Fogarty, Kylie; Baldick, Joe; Chase, Peter; Arey, Brian J.; Lippy, Jonathan
We previously developed a panel of one-step real-time quantitative reverse transcription PCR (one-step qRT-PCR; hereafter referred to as qRT-PCR) assays to assess compound efficacy. However, these high-cost, conventional qRT-PCR manual assays are not amenable to high-throughput screen (HTS) analysis in a time-sensitive and complex drug discovery process. Here, we report the establishment of an automated gene expression platform using in-house lysis conditions that allows the study of various cell lines, including primary T cells. This process innovation provides the opportunity to perform genotypic profiling in both immunology and oncology therapeutic areas with quantitative studies as part of routine drug discovery program support. This newly instituted platform also enables a panel screening strategy to efficiently connect HTS, lead identification, and lead optimization in parallel.